(untitled) (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY The spectrum of agents available for procedural analgosedation (PAS) in paediatric emergency departments (EDs) has increased over the last few decades, yet the pharmacological agents most used in our ED are ketamine and nitrous oxide (N2O). The aim of this study was to assess which patient characteristics in an ambulatory setting were associated with physicians selecting N2O 70% or ketamine as the sedating agent in our paediatric ED, after N2O 70% was introduced. METHODS Patients aged 0 to 16 years who received PAS in a tertiary children’s hospital ED in 2007 (before N2O 70% implementation) and 2016 (after N2O implementation) were included in this retrospective, single-centre cohort study. Data were collected by querying the outpatient ED database for N2O 70% and ketamine. Obtained data included patient characteristics, procedure type and sedation medication. RESULTS 1168 patients were included; 59.8% (699) were male. The overall mean age was 6.3 (± 4.0) years; in the ketamine subgroup, 4.6 (± 4.0) years and in the N2O subgroup, 7.8 (± 3.4) years. In 2016, N2O was chosen in 86.7% of cases involving children aged 4 to 16 years, compared to 28.5% of cases involving children three years and younger. The most apparent shift from ketamine to N2O occurred in patients with displaced upper extremity fractures, with an increase of N2O 70% from 0% in 2007 to 90.8% in 2016. CONCLUSIONS The use of ketamine PAS shifted to N2O PAS, especially in children older than three years and for the reduction of displaced upper extremity fractures.